Outcomes from the Delphi process of the Thoracic Robotic Curriculum Development Committee. (25th January 2018) - Veronesi, Giulia; Dorn, Patrick; Dunning, Joel; Cardillo, Giuseppe; Schmid, Ralph A; Collins, Justin; Baste, Jean-Marc; Limmer, Stefan; Shahin, Ghada M M; Egberts, Jan-Hendrik; Pardolesi, Alessandro; Meacci, Elisa; et al.
Abstract: OBJECTIVES: As the adoption of robotic procedures becomes more widespread, additional risk related to the learning curve can be expected. This article reports the results of a Delphi process to define procedures to optimize robotic training of thoracic surgeons and to promote safe performance of established robotic interventions as, for example, lung cancer and thymoma surgery. METHODS: In June 2016, a working panel was spontaneously created by members of the European Society of Thoracic Surgeons (ESTS) and European Association for Cardio-Thoracic Surgery (EACTS) with a specialist interest in robotic thoracic surgery and/or surgical training. An e-consensus–finding exercise using the Delphi methodology was applied requiring 80% agreement to reach consensus on each question. Repeated iterations of anonymous voting continued over 3 rounds. RESULTS: Agreement was reached on many points: a standardized robotic training curriculum for robotic thoracic surgery should be divided into clearly defined sections as a staged learning pathway; the basic robotic curriculum should include a baseline evaluation, an e-learning module, a simulation-based training (including virtual reality simulation, Dry lab and Wet lab) and a robotic theatre (bedside) observation. Advanced robotic training should include e-learning on index procedures (right upper lobe) with video demonstration, access to video library of robotic procedures, simulation training, modular console training to index procedure, transition to full-procedure training with a proctor and final evaluation of the submitted video to certified independent examiners. CONCLUSIONS: Agreement was reached on a large number of questions to optimize and standardize training and education of thoracic surgeons in robotic activity. The production of the content of the learning material is ongoing.